Application of Virtual Fields Method to Composite Plate Bending Problem - Kashif, Syed Muhammad (IIUM Press, 2011)
This chapter discusses the application of virtual fields method to the case of a thin composite plate in bending. The idea is to use the formulation of virtual fields defined over the specimen such that a single carefully designed test can lead to direct identification of all the six unknown bending rigidities. This represents an application and exploitation of full field data for the characterization of composite materials. This chapter develops the basic mathematical formulation of the working principle of the method adapted to case of composite plate in bending.